NILAI SIRI’ NA PACCE SEBAGAI ALTERNATIF PENYELESAIAN TINDAKAN PERSEKUSI - Hijriani Hijriani; Herman Herman (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
The increasing cases of persecution have led to the building of negative image and public distrust of the state and the law enforcement process. Persecution, as an act that is harmful, troubles, and oppresses others, is included as a criminal offense. The Makassarese recognizes shame culture as a part of the siri cultural system. It is completed by empathy in the concept of pace. Both are referred by the term siri’ na pacce. This value can be implemented and developed to be an alternative to settle the cases of persecution. It is in line with the concept of legal objectives as a philosophy in all aspects of life and obedience to society because it is more entrenched and considered sacred. This study used qualitative research and normative juridical methods. This study aims to find weaknesses and strengths of the value of siri’na pacce as a new alternative to settle persecution in realizing justice and building social harmonization within society. The results reveal that re-instilling the siri culture can be a valuable effort to restraint someone from performing an act of persecution. People can be prevented and prohibited to do such act by adhering to customary rules. It is expected that upholding the siri’na pace value can strengthen the motivation of social solidarity. Therefore, the cultural value is expected to be maintained and becomes an alternative to settle persecution cases, considering that it is more effective and efficient because the community can accept it easily.Nilai Siri’ Na Pacce sebagai Alternatif Penyelesaian Tindakan PersekusiAbstrak Meningkatnya kasus persekusi menyebabkan terbangun stigma negatif dan ketidakpercayaan publik terhadap negara dan proses penegakan hukum. Persekusi sebagai tindakan kejahatan menyakiti, untuk mempersusah dan menumpas orang lain termasuk sebagai tindak pidana. Nilai malu sebagai bagian dari sistem nilai budaya Siri’ dan nilai pedih karena melihat penderitaan orang lain, menjadikan konsep Pacce tampil berpadanan menjadi siri’ na Pacce. Nilai tersebutdapat diimplementasikan dan dikembangkan menjadi alternatif penyelesaian persekusi  karena sesuai dengan konsep tujuan hukum sebagai falsafah dalam segala aspek kehidupan dan ketaatan masyarakat karena lebih mengakar dan dianggap sakral. Artikel ini menggunakan penelitian kualitatif dan metode yuridis normatif. Adapun tujuan penelitian ini untuk menemukan kelemahan dan kelebihan nilai Siri’ na Pacce sebagai alternatif baru penyelesaian persekusi dalam mewujudkan keadilan dan membangun harmonisasi sosial dalam masyarakat. Hasil penelitian menunjukkan bahwa dengan menanamkan kembali nilai malu dalam budaya siri’ terutama berfungsi sebagai upaya pengekangan bagi seseorang untuk melakukan tindakan persekusi dapat dicegah serta dilarang oleh kaidah adat dapat menguatkan motivasi solidaritas sosial dalam penegakan harkat Siri ‘ na Pacce orang lain sehingga diharapkan nilai budaya ini dapat dipertahankan dan menjadi alternatif penyelesaian tindakan persekusi yang pelaksanaannya lebih efektif dan efisien karena mudah diterima masyarakat.DOI: https://doi.org/10.22304/pjih.v5n3.a9